PEMERIKSAAN ANTE-MORTEM DAN POST-MORTEM HEWAN KURBAN DI MUSHOLLAH AL-FAIDAH RSS OESAPA KOTA KUPANG TAHUN 2022 - Elisabet Tangkonda; Chandraone Putra Kefi Amtiran; Yuni Sarah Sidabutar; Angga Dwi Firmanto (Universitas Nusa Cendana, 2023)
To ensure the safety of food components derived from animals, it is necessary to conduct inspections of animals used as sacrifices. ante-mortem and post-mortem inspections are conducted to ensure the safety of meat that will be distributed to the public. The rising number of sacrificed animals at mosques and prayer rooms in Kupang City during Eid al-Adha necessitates the recruitment of additional veterinarians to ensure the safety of the slaughtered animals' meat. In response to this need, the Animal Husbandry Service of the Kupang City Government, in collaboration with the Faculty of Medicine and Veterinary Medicine, conducted inspections of sacrificial animals in mosques and prayer rooms by conducting ante-mortem and post-mortem examinations of animal health and sacrificial meat. The ante-mortem and post-mortem examinations conducted at the Al-Faidah mosque provided positive results, and the final recommendation was that the sacrificed animals were healthy and in accordance with Islamic Sharia. The inspection results indicate that the meat is also suitable for human consumption.